Analisis Kesulitan Belajar Siswa pada Pembelajaran Online MTS Negeri 1 Kolaka - Miswandi Tendrita; Saparuddin Saparuddin; Febrika Febrika (Journal of Creative Student Research, 2023)
The COVID-19 pandemic that has occurred throughout the world, including Indonesia, has greatly impacted teaching and learning activities in schools. The learning process that is usually done face-to-face has now turned into online learning, this underlies the emergence of learning difficulties in students. This problem is the background of this research which will see how the difficulties of students in online learning. This study aims to determine student learning difficulties in the online learning process during the covid-19 pandemic in class VIII at MTs Negeri 1 Kolaka. The type of research used in this research is descriptive qualitative research. The number of samples used were 50 students of class VIII MTs 1 Kolaka taken by random sampling technique. The instrument used in this study is a questionnaire with a total of 20 statement items. Students' learning difficulties can be seen from 3 indicators, namely technical difficulties, implementation of learning and difficulties of external factors. The results of this study indicate that the technical difficulty indicator is 36% in the "very high" category. Indicators of learning implementation 38% in the "medium" category. The external factor difficulty indicator is 40% in the “high” category. Overall the average. of the questionnaire data obtained was 58.22% with the highest percentage of 40% being in the "medium" category. Based on the results of the analysis, it can be concluded that learning difficulties in online learning are moderate.